O Mosteiro de Sta. Maria da Vitória e a vocação moralizante das gárgulas do panteão duartino - Barreira, Catarina Fernandes (2014)
The Portuguese monument called Batalha’s monastery has occupied an important place in Art History especially the unfinished chapels destined to be the Pantheon of the King D. Duarte. There we observe some interesting gargoyles, moral representations as an approach to the late medieval imaginary in the national context, but also common with the thoughts of King D. Duarte. Gargoyles mirrored the daily life of medieval men and women and displayed the confrontation between the religious and the social spheres by criticizing the behaviour of the sinful body, taking on an important educational role amongst audiences. This article aims to understand the moral sense and sexual behaviour that can observe in these gargoyles and its relation with the book Leal Conselheiro, written by D. Duarte some decades before.